Os olhares de João Sebastião Francisco da Costa sobre a cidade de Cuiabá - Davies, Silvia Mara (2023)
This thesis, enrolled in the research line "Contemporary Poetics" within the Contemporary Culture Studies Postgraduate Program, at the Federal University of Mato Grosso, Cuiabá Campus – UFMT, focuses on the work of João Sebastião Francisco da Costa (1949-2016), an artist from the state of Mato Grosso, whose work is permeated with several iconographic symbols of Cuiabá's popular culture. The visual arts landscape in Cuiabá, Mato Grosso's capital, has gained fundamental importance in shaping an iconographic repertoire, constituting forms of identification through varied artistic representations, also through ethnic and cultural diversity. This study aimed to investigate the techniques and theoretical foundations that guide João Sebastião's works concerning his perspectives on the city of Cuiabá, based on the following theoretical frameworks: Brandão (2012), Beltrão (2014), Bertoloto (2006, 2009, 2016), Derdyk (2010), Figueiredo (1979, 2010, 2014, 2021), Guimarães (2007, 2012), Moreira (2006, 2016) and Leite (2003). The methodology adopted is bibliographical study using multiple research techniques, such as: field research, interviews, photographic records, as well as the selection and analysis of artworks from the artist's collection. The analysis followed a descriptive and then an analytical approach, covering the compositional elements, the formal aspects, and the symbolic elements. The thesis is organized into five chapters: the first involves bibliographic studies and photographic research investigating the artist's history. The second chapter is divided into two sections: the first deals with the stages of children's graphics and the importance of artistic activities in the artist's childhood; the second section emphasizes the role of his mother, Dona Alexandra Barros da Costa (Cuiabá, 1915-2011), as a supporter in João Sebastião's artistic growth. The third chapter presents the artist's journey in acquiring technical knowledge in visual arts and his involvement in setting up the UFMT Museum of Art and Popular Culture – MACP. The fourth chapter addresses issues related to symbolic representations of Cuiabá and environmental concerns present in the artworks. The fifth chapter presents the Transmitologismo – João e Maria project, significance as it was João Sebastião's final project. This doctoral thesis "dreamed" and sought to investigate the theoretical and analytical foundations of the artist's productions, capturing his imagination about the city of Cuiabá, and emphasizing his art throughout academic research. In short, the research carried out in this thesis shows the importance and relevance of João Sebastião's works. The artist's gaze passes through the heart, travels along memories, and transfers them from a perspective and a way of doing things that only he was able to achieve.